2020
DOI: 10.1002/er.5976
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole nanowires as a cathode microporous layer for direct methanol fuel cell to enhance oxygen transport

Abstract: Summary Microporous layers (MPLs) have a crucial effect on the performance of direct methanol fuel cells (DMFCs). High polytetrafluoroethylene (PTFE) loading is normally adopted to remove water in a conventional cathode MPL based on carbon black, which hinders oxygen transport and increases ohmic resistance. In this study, we report a novel cathode MPL based on polypyrrole nanowires, which were grown on hydrophobic carbon paper via in situ electropolymerization. Compared with carbon black, the unique structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Methanol is marginally toxic and, therefore, safety measures should be ensured when using it, particularly in fuel cell technologies 36,37 . The anode catalysts of DMFCs typically dwell of dual alloys, reported as farther effective than single metals 38 . Various categories of catalysts have been investigated to enhance the anode electrochemical reaction; examples of these catalysts are as follows: Pt‐Ru, 39,40 Pd‐Ni, 41 Pt‐Sn, 42,43 Pt‐Pd, 44,45 Pt‐Ni, 46 Pt‐Ru‐Ni, 47 Pt‐Vi, 48 Pt‐Mo, 49 Pt‐Au 50 , and Pt‐TiO 2 51,52 .…”
Section: Class Of Dlfcmentioning
confidence: 99%
“…Methanol is marginally toxic and, therefore, safety measures should be ensured when using it, particularly in fuel cell technologies 36,37 . The anode catalysts of DMFCs typically dwell of dual alloys, reported as farther effective than single metals 38 . Various categories of catalysts have been investigated to enhance the anode electrochemical reaction; examples of these catalysts are as follows: Pt‐Ru, 39,40 Pd‐Ni, 41 Pt‐Sn, 42,43 Pt‐Pd, 44,45 Pt‐Ni, 46 Pt‐Ru‐Ni, 47 Pt‐Vi, 48 Pt‐Mo, 49 Pt‐Au 50 , and Pt‐TiO 2 51,52 .…”
Section: Class Of Dlfcmentioning
confidence: 99%
“…Water flooding in a DMFC is commonly ascribed to a lack of hydrophobicity in the cathode GDL/MPL due to the dispersion of the poly-tetrafluoroethylene (PTFE) additive [213]. However, emphasizing the loss of GDL hydrophobic character as the sole reason over such an early phase of cathode flooding acceleration led to a misinterpretation of the precise accelerated rate of structural changes of GDL and potentially trigger an overlook of the significant contribution by morphological changes in the CCL [214]. In a study, using the Sessile-drop method, it is observed that decreasing hydrophobicity leads to a small contact angle of water droplets in the GDL fibers [215].…”
Section: Influence Of Water Flooding In Mea Degradationmentioning
confidence: 99%
“…13 There are numerous studies in the literature, which focus on the effects of MPL composition aimed at improving the performance of the fuel cell. [14][15][16][17][18][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Furthermore, there are many investigations on the MPL, which can be characterised by the type and loading of the hydrophobic agent used 1,14,15,[19][20][21][22][23][24]31 and the carbon powder type used. 1,[15][16][17][18][19][25][26][27][28][29][30]32 Gas permeability is one of the key properties of the PEFC porous media, which describes how effective the convective gas transport is within the porous regions of the fuel cell and accurate values of permeability are needed to obtain realistic saturation profiles in PEFC models.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies in the literature, which focus on the effects of MPL composition 14‐34 aimed at improving the performance of the fuel cell 14‐18,20‐34 . Furthermore, there are many investigations on the MPL, which can be characterised by the type and loading of the hydrophobic agent used 1,14,15,19‐24,31 and the carbon powder type used 1,15‐19,25‐30,32 .…”
Section: Introductionmentioning
confidence: 99%